Mutações no gene TP53 e suas implicações em processos de tumorigênese - Pezzini Martins, Amanda (2023)
The TP53 gene, known as the “guardian of the genome”, encodes the p53 protein responsible for ensuring cellular integrity, inducing apoptosis of cells with changes in the genetic material. p53 dysfunction leads to the proliferation of mutated cells, which can result in a process of carcinogenesis. The present article aims to identify the relationship between mutations in the TP53 gene and oncogenesis processes. This is a narrative bibliographic review of the literature carried out based on articles published between 2005 and 2023 available in the PubMed, MEDLINE and Google Scholar databases in association with virtually available biobanks, such as Clinvar - NCBI. Different types of mutations in the TP53 gene have been identified, such as point mutations (SNP), copy number variations (SNP, CNVs) and insertion/deletion (InDel), which are related to changes in protein function and in the carcinogenesis process of neoplasms such as colorectal, lung and breast cancer. Studies have confirmed the relationship between mutations in the TP53 gene and oncogenesis processes, however it is difficult to measure the role of mutations in the prognosis of the disease, since cancer is a multifactorial disease that encompasses genetic and environmental factors.